Designing a comparable worth based job evaluation system: failure of a priori approach - Tompkins, Jonathan; McEwen, John H.; Brown, Joyce
The State of Montana recently embarked on a project to develop of a new job evaluation system explicitly embracing recommendations emerging from the comparable worth literature. The State's experience shows that while establishing a single, point-factor job evaluation system using a priori approach may make sense from a pay equity perspective, such a system will not necessarily serve an organization's political and administrative objectives. A policy-capturing approach corrected to remove gender bias may prove a better means of pursuing the goal of pay equity
Keywords: Job Evaluation; Job Analysis